Video dengan Sulih Teks Dalam Meningkatkan Efektivitas Iklan - Scott Daniel Habibuw; Irwansyah Irwansyah (Inter Komunika, 2019)
The use of subtitle is now familiar in a film or video. MP Clinic, one of the aesthetic clinics in Jakarta uses subtitle as a way to increase the effectiveness of its advertisements. This study aims to show the use of text substitution in the same language (SLS) on video has a difference in increasing the effectiveness of advertising measured by the Hierarchy of Effect Model. This research was conducted by the experimental method, by dividing the experimental participants into two groups, namely group A (subtitled video) and B (video without subtitle). Hypothesis testing shows the comparative t count of 4.03 (SD = 0.41494: sig = 0.5) is greater than the t table (0.681). This means that there are differences between groups of video participants who use subtitle and groups of video participants who do not use subtitle. Differences are also shown from the results of the mean effectiveness of advertising. The mean number of the group of participants using subtitle (m = 4.18) is greater than the mean (m = 3.58) of the group of participants who do not use subtitle. Thus, the use of subtitle on the video has been proven to increase the effectiveness of an advertisement.